Mapping Of Legal Construction Of Agreements Between Customers And Conventional Banks Vs. Sharia Bank On Accusations Of Riba - Ahmad Sukron; Wiwin Ariesta (Sean Institute, 2024)
So far, Muslims have often been confronted in the name of religion in the struggle for market share. In the banking world, Muslims have indirectly been taught that transaction agreements between customers and conventional banks contain usury which is prohibited by religion. The prohibition of usury is agreed upon by consensus of the ulama, but the ulama differ in determining the illat that makes usury haram, resulting in differences in providing definitions, determining the types of usury and determining the elements of usury from each type, let alone assessing the practice of bank interest as usury, therefore This research is needed to find out what transactions contain usury and which do not contain usury, the researcher chose the Shafi'i school of thought in studying the concept of usury because the majority of Muslims in Indonesia are Shafi'iyah and the Shafi'iyah explanation is more detailed in discussing usury, the results of the research found that group of textual and contextual views regarding the conventional bank interest system is haram and classified as usury qordhun provided there is a benefit for the debtor or the amount of interest required in the transaction, but not all transactions in conventional banking are haram usury, because there are many other transactions such as savings, transfers money and so on which are not included in the concept of usury. The researcher's suggestion is that a revision of the Compilation of Sharia Economic Law (KHES) is needed. So far, KHES has explicitly mentioned twice in Articles 576 and 585 paragraph 2 that conventional banking institutions are ribawi institutions, while usury is not an institution but a debt or buying and selling transaction that contains illat. and elements of usury, so that not all transactions in conventional banking have illat and elements of usury.